Review of Vasil Simonenko's work - Савчук, Григорій Олегович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
In the paper the work of Vasyl Symonenko (lyric poetry, lyro epic, short stories) is integrally analysed. Attention to collections "Bank of expectations" and "For itself" is paid. The romantic features of lyric poetry, preparation of lyric hero to adult life, feeling of responsibility are marked. The verses of these collections help an author to attain an emotional equilibrium, perform the original psychotherapy duty. First printed collection "Silense and thunder" educed the updating of poetic maintenance at maintenance of classic forms. The poles of "silense" (intimate lyric poetry) and "thunder" (civil lyric poetry) are analysed, didacticism and gnomic are marked. The posthumous collection "Earthly gravitation" strikes the "overpopulation" of the verse line, the concentration of idea, the transparency of ideas, the faith in the future. The features of address verses, facilities of fight against the negative public phenomena are studied. During the study of lyric poetry of V. Symonenko non-verbalized motives of aspiring to the changes, aspiration and spiritual way are educed. Romanticism of lyric poetry is consonant with short stories of V. Symonenko, collected in a book "Wine from roses". The plot organization and ideological level of short stories "He interfered with her to sleep", "Wine from roses", "Black horseshoe" are analysed. An accent on the open finales of works is done.The fairy-tales of the sixty contain a political implication, but they could be addressed to the junior reader. For more complete understanding of the artistic world of author it is necessary to know his literary-critical work, foremost the article "Beauty without beauties ", sanctified to the poetry of L. Kostenko. V. Symonenko appears in the hypostasis of professional reader that analyses collection "Trip of heart". V. Symonenko noticed beauty, wisdom, thin heartfelt sensitiveness and good taste, could be said about a critic. The conclusion, that a poet kept straight in life, and in work, as well as majority of sixties is drawn.